(untitled) (Jurnal Destinasi Pariwisata, 2025)
The development of social media can be a promotional tool with its wide range. Social media has proven to be a part needed by corporate institutions in reaching customers. In the tourism sector, social media can also be used as a promotional media for various tourist attractions. Stakeholders can use social media to promote tourist attractions in their area. One of the popular social media is Instagram with its users dominated by Generation Z. Jember Mini Zoo maximizes the use of social media in introducing and promoting its attractions. The purpose of this study is to analyze the influence of Instagram social media on Generation Z’s regarding the decision to visit Jember Mini Zoo tourist attraction. This study uses a quantitative approach with data collection carried out through observation, questionnaires and documentation. The sampling technique used was purposive sampling by distributing questionnaires to 100 representative respondents. The data analysis technique of this study used a questionnaire test that included validity and reliability tests, simple linear regression analysis and t-test calculated with IBM SPSS Statistics 27. Based on the data analysis, it can be concluded that Instagram social media has a positive effect on Generation Z’s decision to visit Jember Mini Zoo with a correlation value of 0.636 and the contribution value of Instagram’s influence on Generation Z’s decision to visit Jember Mini Zoo of 40.5%. Thus, the existence of Instagram social media managed by Jember Mini Zoo has a significant effect on the decision to visit, this is in line with the significant increase in the number of visits and followers at Jember Mini Zoo.